The Effect of Providing Moringa Leaf Flour (Moringa oleifera) in Feed as a Feed Additive on Increasing the Performance of Super Village Chickens (Gallusgallus domesticus L. variation joper) - Saragih, Winda; Manalu, Carlos Marianus; Umar, Sayed; Hanafi, Nevy Diana (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2025)
Joper chickens are breeds of kampung chickens, Bangkok chickens, or other local breeds of chickens separated from purebred chickens. In addition to genetic factors and feed management, the use of natural constituents as feed additives can affect the meat quality of super hens. Feed additives are ingredients that do not include food substances that are added to the stove in small amounts and are aimed at spurring growth and increasing feed efficiency. The existence of various studies in the selection of feed raw materials that produce quality feed additives that are easy to use and cheap to meet the needs of super rural chickens are moringa leaves. The design used in this research was a Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatment consisted of T0 (Ration does not contain Moringa leaf flour), T1 (Ration contains 6% Moringa leaf flour), T2 (Ration contains 9% Moringa leaf flour), T3 (Ration contains 12% Moringa leaf flour), The parameters observed were feed consumption, body weight gain and feed conversion. The results showed that Moringa leaf flour had a significant effect on feed consumption, body weight gain and feed conversion. The best results were obtained in treatment T1, namely the ratio containing 6% Moringa leaf flour, which was able to increase feed consumption by 367.46 grams, body weight gain by 88.62 grams and feed conversion ratio by 4.16.